Flavonoids, Isoquinoline Alkaloids, and Their Combinations Affect Growth Performance, Inflammatory Status, and Gut Microbiome of Broilers Under High Stocking Density and Heat Stress - Kittisak Insawake; Thaweesak Songserm; Ornprapun Songserm; Yongyuth Theapparat; Kazeem D. Adeyemi; Konkawat Rassmidatta; Yuwares Ruangpanit (Animals)
High stocking density (HSD) and heat stress (HS) challenge broiler production. While antibiotics can mitigate the adverse effects of HS and HSD, their restricted use underscores the need to explore phytochemicals, particularly their combined effects under such conditions. This study investigated the influence of flavonoids, isoquinoline alkaloids, and their combinations as alternatives to bacitracin on growth performance, inflammatory status, gut morphology, and ceca microbiome in broilers raised under HSD and HS. A total of 2100 one-day-old male Ross 308 broiler chicks were distributed into 70 replicates, randomly assigned to one of seven dietary treatments and raised during the summer for 37 days. The treatments included normal stocking density (NSD, 10 birds/m2); HSD (15 birds/m2); HSD + 50 ppm of bacitracin (BCT); HSD + 300 ppm of flavonoids (FVNs); HSD + 80 ppm of isoquinoline alkaloids (IQAs); HSD + FVNs (1–10 days) and IQAs (11–37 days) (FVN-IQA); and HSD + IQAs (1–10 days) and FVNs (11–37 days) (IQA-FVN). The HS index reached or exceeded 160 during most of the experimental period. From 11 to 24 days of age, the HSD and BCT birds had lower body weight gain. The FVNs, IQAs, and their combinations decreased the corticosterone, IL-6, malondialdehyde, and heterophil–lymphocytes ratio compared to the HSD. Jejunal, ileal, and duodenal villi height/crypt depth ratio was lower in HSD than in other treatments except BCT. The α- and β-diversity, microbiota composition, and metabolic pathways were affected by treatment groups. Overall, FVNs, IQAs, and their combinations improved the growth performance, anti-inflammatory response, and gut health in broilers under HSD and HS, with the combinations exerting synergistic effects.